Pancreatic cancer cell-intrinsic transglutaminase-2 promotes T cell suppression through microtubule-dependent secretion of immunosuppressive cytokines - Anton Wellstein; Thomas Seufferlein; Alexander Kleger; Tim Eiseler; Anton Lahusen; Nora Minhöfer; Kim-André Lohse; Christine Blechner; Jessica Lindenmayer; Sabine Windhorst; Yuan-Na Lin (Journal for ImmunoTherapy of Cancer)
Background Pancreatic ductal adenocarcinoma (PDAC) is mostly refractory to immunotherapy due to immunosuppression in the tumor microenvironment and cancer cell-intrinsic T cell tolerance mechanisms. PDAC is described as a “cold” tumor type with poor infiltration by T cells and factors leading to intratumoral T cell suppression have thus received less attention. Here, we identify a cancer cell-intrinsic mechanism that contributes to a T cell-resistant phenotype and describes potential combinatorial therapy.Methods We used an unbiased screening approach of T cell resistant and sensitive murine KPC (KrasLSL-G12D/+; Trp53fl/fl; Ptf1aCre/+) PDAC cells in a three-dimensional co-culture platform with syngeneic antigen-educated T cells to identify potential cell-intrinsic drivers of T cell suppression in PDAC. Comparative transcriptomic analysis was performed to reveal promising candidates that mediate resistance to T cells. We investigated their contribution by shRNA-mediated knockdown and pharmacological inhibition in murine in vitro and in vivo studies, as well as in patient-derived organoids (PDOs). A combination of transcriptomic analyses, cytometric and immunohistochemistry techniques allowed us to validate the underlying T cell response phenotypes of PDAC cells. The action of TGM2 via interaction with tubulin and the impact of microtubule dynamics and vesicle trafficking were evaluated by protein analyses and live-cell imaging. Correlation analyses via TCGA data complemented the functional studies.Results We identified transglutaminase 2 (TGM2) as a mediator of T cell suppression in PDAC. We report that high levels of TGM2 expression in patients’ tumors correlate with immunosuppressive signatures and poor overall survival. We found that TGM2 regulates vesicle trafficking by modulating microtubule network density and dynamics in pancreatic cancer cells, thus facilitating the secretion of immunosuppressive cytokines, which impair effector T cell functionality. In TGM2-expressing PDOs, pharmacological TGM2 inhibition or treatment with nocodazole increased T cell-mediated apoptosis. Also, pretreatment of TGM2high PDOs with sublethal doses of the spindle poisons paclitaxel or vincristine increased CD8+T cell activation and sensitized PDOs toward T cell-mediated cytotoxicity.Conclusions These findings indicate that targeting microtubular function therapeutically may enhance antitumor T cell responses by impacting activity of immunosuppressive cytokines in the PDAC microenvironment.